Monitoring patients with systemic lupus erythematosus: general characteristics and discussion questions (according to the Canadian Rheumatology Association recommendations) - T. A. Panafidina; T. V. Popkova; S. K. Solovyev (Научно-практическая ревматология)
The paper details 15 new recommendations of the Canadian Rheumatology Association for the clinical monitoring of patients with systemic lupus erythematosus (SLE). During their development, the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) classification system for rating the quality of recommendations was used for the first time. The recommendations for physician specialization; cardiovascular risk assessment; anti-Ro/SSA and anti-La/SSB antibody concentrations examination during pregnancy; and annual influenza vaccination are considered to be strong; those for rating disease activity and damage index; ultrasound of the carotid arteries; diagnosis of osteoporosis and osteonecrosis; Doppler ultrasound of uterine and fetoplacental blood flow during pregnancy; screening for cervical cancer, viral hepatitis B and C in patients with SLE are regarded as conditional.